Risk Factors Associated with Lung Capacity on “XY” Furniture Workers in Sungai Ambawang District - Nurul Kharismadewi; Sunarsieh; Nurul Amaliyah (POLTEKKES KEMENKES PONTIANAK, 2021)
Analysis of risk factors related to furniture worker’s lung capacity of “XY” at Sungai Ambawang district in 2018. The aim of study was knowing the analysis of risk factors related to meubel worker’s lung capacity of “XY” at Sungai Ambawang district in 2018. This type of study was observational with cross sectional study. The sample of this study was 39 men workers. The data were collected by interviews with responden, measurements of respirable dust producing by the work activity and inspections of lung capacity. The data were formed as univariat and bivariat with kruskal-wallis, t-test and chi-square test. The result showed that there was a significant between respirable dust producing by the work activity (p=0,000), years of service (p=0,001), smoking behavior (p=0,020) and history of diseases (p=0,060) with the lung capacity, while there were no a significant are the age (p=0,951) and using of personal protective equipment masks (p=0,060) with the lung capacity. The conclusion from this study that was a significant between respirable dusts of the work activity produces, years of services, smoking behaviors and history of diseases with the meubel worker’s lung capacity of “XY” at Sungai Ambawang district.